The role of after-hours house-call medical service in the treatment of COVID-19 patients awaiting hospital admission: A retrospective cohort study. Issue 6 (11th February 2022) - Inokuchi, Ryota; Jin, Xueying; Iwagami, Masao; Ishikawa, Masatoshi; Tamiya, Nanako
Abstract : Abstract: Due to the increasing number of coronavirus disease 2019 (COVID-19) cases in Japan, hospitals are unable to provide admission and immediate inpatient care. The after-hours house call (AHHC) service offers telephone consultations and in-home care to patients awaiting admission. Currently, there is no report on the management of COVID-19 patients when inpatient beds are insufficient. We aimed to describe the clinical characteristics and outcomes of COVID-19 patients treated by an AHHC medical service in Osaka and Tokyo, between April and May 2021 (during the fourth wave in Japan). Patients were classified into 2 groups: Moderate I and Moderate II, according to the severity of infection under Japanese guidelines. A retrospective study of the hospital records and follow-up telephone consultations was performed. The AHHC treated a total of 55 COVID-19 patients (17 with Moderate I, 38 with Moderate II disease). The median ages (interquartile range) were 63 (49–80.5) and 64 (50.8–81), respectively. In each group, approximately 30% of AHHC patients received out-of-hospital oxygen therapy for the duration of their treatment until it was no longer required. Major symptoms, including shortness of breath or difficulty breathing (47.1% and 78.9%, respectively) and fever or chills (41.2% and 76.3%, respectively) were lower in the Moderate I group than in the Moderate II group. Overall, 16.4% of patients died, with 17.6% in the Moderate I group and 15.8% in the Moderate II group. We found the proportion of mortality in patients treated by the AHHC was slightly higher to that of patients treated in Japanese hospitals. This study will provide an alternative management of patients requiring oxygen in situations where hospital beds are in short supply.